Invasi Śriwijaya ke Bhumijawa: Pengaruh Agama Buddha Mahayana dan Gaya Seni Nalanda di Kompleks Percandian Batujaya* - Djafar, Hasan (Pusat Penelitian Arkeologi Nasional, 2014)
Paper ini membahas pengaruh invasi Śrīwijaya ke Bhūmijāwa (Tārumanāgara) pada akhir abad ke-7 M. Fokus pembahasan adalah pengaruh Agama Buddha Mahāyāna dan gaya seni Nālandā di kompleks percandian Batujaya, Karawang, Jawa Barat. Hasil penelitian di Batujaya selama periode 1985-2006 telah menghasilkan beberapa bukti baru penyebaran Agama Buddha Mahāyāna dan gaya seni Nālandā di Kompleks percandian Batujaya. Abstract. The Invasion of Śrīvijaya to Bhūmijāwa: Influence of Mahāyāna Buddhism and Nālandā Art Style in The Temple Complex of Batujaya. This paper discusses the influence of Śrīvijaya invasion to Bhūmijāwa (Tārumanāgara) in the late 7th Century C.E. The focus of discussion is the influence of Mahāyāna Buddhism and the art style of Nālandā in the temple complex of Batujaya, Karawang, West Java. The results of the archaeological research conducted at Batujaya site area during the period of 1985-2006 has yielded some new evidence on the spread of Mahāyāna Buddhism and the art style of Nālandā in that area.